معراج النبی ﷺ کے متعلق مرزاقادیانی کا نظریہ؛ عقلی و نقلی استدلال کا علمی جائزہ: Mirza qadiani’s Theory of Miraj-ul-Nabi ﷺ: A Scientific Review of Rational and Reported Reasoning - Fareed ud Din, Dr.Hafiz; Mahboob, Dr.Muhammad Sajid (Al-Amīr Research Journal for Islamic Studies, 2024)
Mirza Ghulam Ahmad Qadiani claimed that According to the Hadiths which reported about the descending of Jesus is not means the Israeli Massiah, but the Muhammadan Massiah (Mirza Qadiani) in the form of Messiah Ibn Maryam. So, he (Mirza Qadiani) himself is the "Promised Messiah". Because Jesus Ibn Maryam (AS) was crucified by the Jews and later his disciples took him down from the cross alive and wrapped him in a bandage and he came to Srinagar Kashmir fir the purpose of preaching and died a natural death there. His grave is also in Kashmir. The meaning of the verse of Christ’s ascension in the Holy Qur’an is that he was spiritually lifted up to heaven, no human being can be physically lifted up to heaven. In view of this belief, he has also denied the physical Ascension of the Prophet ﷺ, that he did not go to the sky physically, but went spiritually, meaning that he received the highest level of Kashf, and he (Mirza Qadiani) also has the knowledge and experience of this rank. According to Mirza Qadiani, it is logically impossible for a human body to go to the heavens with an elemental body. Below, a brief critical review of this false theory of Mirza Qadiani will be presented in the light of Quran o Hadith and with rational reasoning. Key words: ‘Īsā, Qādiyānī, Masīh e Maw‘ūd, Me‘rāj, Ascending, Descending, Kashf.